Obtenção e análise de dados de maquinário agrícola e meteorológico - Favero, Rafael Antônio (2024)
The present work aims to develop a hardware and software prototype that enables the capture and subsequent analysis of data from agricultural and meteorological machinery. On the one hand, hardware will be developed that provides reading data via CAN from devices related to agricultural machinery, on the other The aim is to capture data relating to the climate, and display it via a browser on a local network. Put The aim is to unite these aspects and create visualizations providing data analysis that help to understand the relationship between the functioning of agricultural machinery and climatic aspects, contemplating a new perspective on their functioning, and offering an opportunity to, based on the collected and analyzed data, propose improvements in hardware and software then used in agricultural reality.